2018
DOI: 10.13189/ujer.2018.060709
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Opinions on Use of Self-Regulation Strategies at Science and Art Centers: Turkey Sample

Abstract: The purpose of this study is to identify the usage status of self-regulation strategies at Science and Art Centers (BİLSEMs) that provide the gifted students with education in Turkey. This research was designed within qualitative study and survey model was used. It was conducted with 24 teachers at Science and Art Centers each in the Western Black Sea, Marmara and Aegean regions in Turkey. The teacher interview form designed by the researchers was used as the data collection instrument. Descriptive analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…(2011) also confirmed that there is a strong positive relationship between teachers' self-regulation and their job performance and their effectiveness. But this study result seems better in the implementation of self-regulated science teaching than the study results conducted in other countries which says teachers are not competent enough to implement self-regulated teaching due to lack of motivation and meta-cognitive strategies ( Eker & Ince, 2018 ; Peeters et al.,2014 ); teachers' self-regulation in higher education. are not as self-regulated, planned, reflective, or spiral as some assume; the knowledge they have and their classroom practice is low ( van Eekelen et al., 2005 ; and Spruce and Bol, 2014 ).…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…(2011) also confirmed that there is a strong positive relationship between teachers' self-regulation and their job performance and their effectiveness. But this study result seems better in the implementation of self-regulated science teaching than the study results conducted in other countries which says teachers are not competent enough to implement self-regulated teaching due to lack of motivation and meta-cognitive strategies ( Eker & Ince, 2018 ; Peeters et al.,2014 ); teachers' self-regulation in higher education. are not as self-regulated, planned, reflective, or spiral as some assume; the knowledge they have and their classroom practice is low ( van Eekelen et al., 2005 ; and Spruce and Bol, 2014 ).…”
Section: Discussioncontrasting
confidence: 72%
“…However, teachers are not competent enough to implement selfregulated teaching due to lack of motivation and meta-cognitive strategies (Peeter et al, 2014, &Eker and_ Ince, 2018). Van Eekelen et al ( 2005) also confirmed that teachers' self-regulation in higher education is not as self-regulated, planned, reflective, or spiral as some assumes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data relating to the scales used in the study were collected with the "Perceived Role Models Scale" and "Self-Regulation Scale for Science", which were developed during the first author's doctoral dissertation study, and validity and reliability checks were performed (Karaca & Bektas, 2022). To determine the scale items, the authors created a pool of questions based on the literature (Eker & İnce, 2018;Ilgaz & Gül, 2014;Kayan Fadlelmula, 2011;Zimmerman & Martinez-Pons,1986). Karaca and Bektas (2022) created selfregulation scale items based on Zimmerman's (1986) self-regulation model and strategies.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…The studies listed above show how important self‐regulation is to find answers to such questions. On the other hand, most of the research in the literature is conducted with groups such as teachers (Capa Aydin et al, 2009; Eker & İnce, 2018; Pamuk et al, 2017; Sutton, 2007) and teacher candidates (Demir & Doganay, 2019; Mataka, 2014; Ning & Downing, 2012), high school and university students (Fouche, 2013). It is seen that studies at the school level are also mostly conducted based on quantitative research methods (Tosun & Sekerci, 2015; Yerdelen & Sungur, 2019).…”
Section: Introductionmentioning
confidence: 99%